2014
DOI: 10.1021/jp501560u
|View full text |Cite
|
Sign up to set email alerts
|

Role of Co Clusters and Oxygen Vacancies in the Magnetic and Transport Properties of Co-Doped In2O3 Films

Abstract: The (In1–x Co x )2O3 films with x = (0.055, 0.08, 0.10, 0.15) have been prepared by a radio frequency magnetron sputtering technique and investigated by X-ray diffraction, X-ray photoelectron spectroscopy, X-ray absorption fine structure, Hall effect, and room-temperature magnetic measurements. The detailed structural analyses and full multiple-scattering ab initio calculations indicate that most Co2+ ions substitute for In3+ sites of In2O3 lattice and form CoIn2+ + VO complexes with the O vacancy in the near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…When lattice ions are replaced by doping ions, in contrast to their incorporation into the intercrystallite space, the emerging vacancies can form complexes with these ions. Such complexes were characterized for In 2 O 3 nanocrystals doped with Mn +2 and Co +2 ions [48]. The vacancies formed when these ions are included in the In 2 O 3 lattice, and enter the first coordination sphere of oxygen anions surrounding the doping ion [49].…”
Section: Mechanisms Of Increasing the Sensitivity Of Two-component Si...mentioning
confidence: 99%
“…When lattice ions are replaced by doping ions, in contrast to their incorporation into the intercrystallite space, the emerging vacancies can form complexes with these ions. Such complexes were characterized for In 2 O 3 nanocrystals doped with Mn +2 and Co +2 ions [48]. The vacancies formed when these ions are included in the In 2 O 3 lattice, and enter the first coordination sphere of oxygen anions surrounding the doping ion [49].…”
Section: Mechanisms Of Increasing the Sensitivity Of Two-component Si...mentioning
confidence: 99%
“…[13] As an important semiconductor material, In 2 O 3 has been widely studied in various fields including semiconductor spintronics. Since Philip et al reported the interesting carrier-controlled above room-temperature ferromagnetism (RTFM) in transparent Cr-doped In 2 O 3 thin films, [14] there have been abundant research reports on RTFM in In 2 O 3 -based DMSs [15][16][17][18][19][20] as well as in pure In 2 O 3 . [21] However, most of the research focused on the 3d transition metal (TM) doping, [15][16][17][18][19][20] where TM ions occupy the corresponding lattice sites in the host with a dilute concentration to minimize the possibility of anti-ferromagnetic ordering.…”
Section: Introductionmentioning
confidence: 99%
“…Since Philip et al reported the interesting carrier-controlled above room-temperature ferromagnetism (RTFM) in transparent Cr-doped In 2 O 3 thin films, [14] there have been abundant research reports on RTFM in In 2 O 3 -based DMSs [15][16][17][18][19][20] as well as in pure In 2 O 3 . [21] However, most of the research focused on the 3d transition metal (TM) doping, [15][16][17][18][19][20] where TM ions occupy the corresponding lattice sites in the host with a dilute concentration to minimize the possibility of anti-ferromagnetic ordering. [22] Compared with TMs with open d shells, 4f rare earth (RE) ions may offer the stronger magnetic interaction and anisotropy and thus may possess the larger magnetic moments in doped semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Following the theoretical prediction by Dietl et al of RT ferromagnetism in ZnO-based DMSs [4], various TM elements (Fe, Co, Ni, Mn, Cr) doped wide-band-gap oxide semiconductors appear to be rather promising candidates. Experimental works on TM-doped-ZnO [5][6][7], TiO 2 [8][9][10], SnO 2 [11,12] as well as In 2 O 3 [13][14][15] in bulk, thin film and nano-particle forms have suggested that TMs certainly could be used to dope in host oxide semiconductors to achieve RT ferromagnetism for practical application. Being one of these candidate hosts, In 2 O 3 is an important n-type directband-gap semiconductor ($3.75 eV) with excellent electrical conductivity and high optical transparency.…”
Section: Introductionmentioning
confidence: 99%